Clinical and denture-related characteristics in patients with epulis fissuratum: a retrospective 58 case series - Marzieh Mohammadi; Nader Navabi; Mohammad Reza Zarei (Babol University of Medical Sciences, 2017)
Introduction: Epulis fissuratum is one of the important denture-related mucosal lesions that occurs around the borders of an ill-fitting denture. The purpose of this study was to analyze the cases of epulis fissuratum admitted in the department of oral medicine, Kerman Dental School in relation to the demographic, denture-related and clinical findings. Materials &Methods: Medical files of all patients referred to the Department of Oral Medicine and Oral Pathology, Kerman Dental School, Iran from 1999 to 2014 were reviewed and 58 cases with the diagnosis of epulis fissuratum with complete and acceptable data were illustrated. Results: The frequency of epulis fissuratum was 2.9 % of the total number of pathologies. The disorder had been occurred predominantly in the sixth decade of life (41.4%) and more often among females (79.3%). The frequency of epulis fissuratum was higher for a length of denture use of more than 10 years. Patients reported pain associated with the lesion (70.6%). Conclusion: The knowledge of some facts, especially the quality of dentures and level of denture hygiene in patients with epulis fissuratum supports the importance of the prevention of the lesion, hence the dentists should instruct their patients who have worn dentures how to prevent this lesion.